The Prevalence of Familial Mediterranean Fever and Behçet’s Disease: A Cross-Sectional Study - Özgür ALPARSLAN; Buğra Han EGELİ and Yeltekin DEMİREL and Serdal UĞURLU (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the coexistence of familial Mediterranean fever (FMF) and Behçet’s disease (BD). Patients and methods: This cross-sectional study was conducted between May 2009 and August 2009. The study included 14,881 randomized children (7,741 males, 7,140 females; mean age 13.0 years; range, 12 to 14 years) from sixth to eighth grades, in 72 primary schools in the center of Turkey’s Sivas province. Of these children, 985 were randomly selected and interviewed with their parents. During these interviews, the family trees up to second-degree relatives were drawn. The presence of a diagnosis of FMF or BD was questioned. Patient history, physical examination, eye examination, and pathergy test were performed when needed. The methods of this study were reported in accordance with the STrengthening the Reporting of OBservational studies in Epidemiology guidelines. Results: Nine hundred and eighty-five students, 978 mothers, 953 fathers, and 1,876 relatives (4,792 in total) were included in the study. The ratio of consanguineous marriage ratio was 13.6%. Only 30 patients (0.6%) were diagnosed with FMF, while three (0.06%) were diagnosed with BD. In patients with FMF, consanguineous marriage was statistically significant (p=0.015). In terms of low back, heel, and joint pain and morning stiffness, there was a statistically significant difference between patients with and without FMF (p<0.05). Of the three BD patients, one had concomitant FMF. Conclusion: The prevalence of FMF in Sivas province was higher than Turkey’s prevalence; however, the prevalence of BD was lower. According to these findings, it is not easy to conclude that the two diseases share a common pathogenesis.